2002
DOI: 10.1103/physrevlett.88.257601
|View full text |Cite
|
Sign up to set email alerts
|

Processing Information by Punctuated Spin Superradiance

Abstract: The possibility of realizing the regime of punctuated spin superradiance is advanced. In this regime, the number of superradiant pulses and the temporal intervals between them can be regulated. This makes it feasible to compose a kind of the Morse Code alphabet and, hence, to develop a technique of processing information. 76.20.+q, 76.60.Es, 07.55.Yv, 85.90.+h Spin systems can exhibit a phenomenon that is analogous to atomic superradiance [1,2], because of which it is called spin superradiance. To realize t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…The regime of punctuated spin superradiance was suggested in Ref. 50. The situation for atomic systems is analogous to that for spin assemblies.…”
Section: Dynamics Of Squeezingmentioning
confidence: 92%
“…The regime of punctuated spin superradiance was suggested in Ref. 50. The situation for atomic systems is analogous to that for spin assemblies.…”
Section: Dynamics Of Squeezingmentioning
confidence: 92%
“…This work expands on recent research on superra diance of atoms [6][7][8][9] in that it explores a solvable model, which represents a potentially realizable phys ical system where in addition to the cooperative effects resulting from the close proximity of identical atoms, I am also exploring the effects of the cavity on the sys tem's cooperative decay, a feature which so far has not been explored except in spin superradiance [10][11][12][13][14][15][16][17]. Yukalov and collaborators have shown that the pres ence of a resonator is crucial to spin superradiance.…”
Section: Introductionmentioning
confidence: 96%
“…The possibility of realizing spin superradiance by molecular magnets, coupled to a resonator, was advanced in Ref. [10], being based on the well developed theory [3][4][5][6][7][8][9][10][11]. At the same time, there have appeared speculations that spin superradiance in molecular magnets could be produced without coupling them to a resonant circuit, but in a way completely equivalent to atomic superradiance, so that the collectivization in spin motion would be due solely to their interactions through the common radiation field.…”
Section: Introductionmentioning
confidence: 99%
“…In order to realize spin superradiance, it is necessary to couple a polarized magnet to a resonant electric circuit. The collectivization of spin motion happens due to the resonator feedback field, which, thus, replaces the common radiation field [3][4][5][6][7][8][9][10][11]. The analogies and differences in atomic and spin superradiance have been extensively analysed in reviews [3,4,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation